Regulation of H2A ubiquitination and SLC7A11 expression by BAP1 and PRC1 - Zhang, Yilei; Koppula, Pranavi; Gan, Boyi (Cell cycle (Georgetown, Tex.), 2019)
SLC7A11 (or xCT) imports extracellular cystine into cells to promote glutathione synthesis, thus inhibiting ferroptosis. SLC7A11 expression is tightly controlled in normal cells and its dysregulation results in aberrant expression of SLC7A11 in human cancers. We recently discovered that tumor suppressor BAP1, a H2A deubiquitinase, represses SLC7A11 expression by reducing H2A ubiquitination (H2Aub) on the SLC7A11 promoter. BAP1 inactivation in cancer cells leads to SLC7A11 de-repression, ferroptosis resistance, and tumor development. Here we show that BAP1 promotes ferroptosis induced by class I ferroptosis inducer (FIN) erastin but not by class II FIN RSL3, further supporting that BAP1 regulates ferroptosis through SLC7A11. In addition, we studied how BAP1 coordinates with other transcription factors to regulate SLC7A11 expression and show that BAP1-mediated SLC7A11 repression does not require NRF2 and ATF4 transcription factors. Finally, we show that, while BAP1 decreases whereas PRC1 (a major H2Aub ubiquitin ligase) increases H2Aub binding on the SLC7A11 promoter, both BAP1 and PRC1 represses SLC7A11 expression, suggesting that a dynamic regulation of H2Aub is important for SLC7A11 repression. Together, our data provide additional insights on epigenetic regulation of SLC7A11 expression in cancer cells.